(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
The IGF1 gene (insulin-like growth factor 1) is a candidate gene for marker-assisted selection strategies. This study was designed to identify and analyze various genetic diversity indices within exon 3 region of IGF1 gene in two Nigerian Savannah Muturu cattle populations using PCR-RFLP. 20 Muturu cattle were randomly sampled with 11 samples from Tarka in Benue State and 9 samples from Onueke in Ebonyi State. About 0.2ml of blood was collected from the coccygeal vein of the tail-head of the selected cattle with the use of 1-inch, 18-gauge classic needle and syringe. The blood samples obtained from each cattle was used for DNA extraction and amplification following standard procedures (www.whatman.com). The amplified DNA were digested with the use of SnaB1enzyme and the resultant DNA fragments subjected to Agarose Gel Electrophoresis. Two genotypes (CC and CT) were identified. The genotypic frequencies were 0.95 for CC and 0.05 for CT. A total of 10 Alleles were found with lengths ranging from 300 to 440 base pairs. The allelic frequency ranged from 0.025 to 0.200. The mean number of alleles (Na), mean number of effective alleles (Ne), mean information index (I), mean observed heterozygosity (Ho) and mean expected heterozygosity (He) were 5.000 ±1.000, 3.700 ±0.700, 1.416 ±0.202, 0.045 ±0.045 and 0.720 ±0.053 respectively. This study demonstrates low level of genetic diversity therefore, there is need for genetic improvement and conservation considering the endangered nature of the Muturu cattle breed.